Screening of Anticancer and Immunomodulatory Properties of Recombinant pQE-HAS113 Clone Derived from Streptococcus Equi - Mohammed Al Mohaini, Arshad Farid, Abdulkhaliq J. Alsalman, Maitham A. Al Hawaj, Yousef N. Alhashem, Shakira Ghazanfar, Muhammad Muzammal, Muhammad Hashim Khan, Arezoo Dadrasnia, Salmah Ismail (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Streptococcus equi has been identified to contain the hyaluronan synthase gene (HAS), which could have a role in the cell proliferation activity. The objective of this research was to determine anticancer properties of HAS113 recombinant clone. Methodology: The intracellular and extracellular portions of the expressed gene products of pQE-HAS113 were harvested and evaluate for anticancer properties against prostate cancer cell (PC3) and breast cancer cell (MCF-7). To evaluate anti-proliferative properties of pQE-HAS113, two assays were carried out: MTT assay, which was used for assessing percent cell inhibition and apoptosis assay, through the AO/EB stain of living, apoptotic, as well as necrotic cells. For evaluation of the immunomodulatory properties of pQE-HAS113 on RAW264.7 in terms of IL-6, IFN-γ & IL-8 expression, flow cytometry examination was done. The harvested intracellular and extracellular portions of pQE-HAS113 were tested. Results: The results indicated that the percentage proliferation of both the prostate cancer and breast cancer cells were 2.1% and 7.2% respectively against the intracellular portions of pQE-HAS113. While in case of the extracellular portions of pQE-HAS113 the proliferation rate of both the prostate cancer and breast cancer cells were 6.5% and 6.7% respectively. The PQE-HAS113 intracellular clone gene has shown proinflammatory activity by stimulating the expression of IL-6, INF-γ, & IL-8 in the RAW264.7 macrophage cells. Conclusion: Thus, the results from the present study indicated that the expressed product of recombinant clone of HAS 113, pQE-HAS113 has potential to be used as anti-proliferative and apoptosis inducing substance for prostate and breast cancer.